Polysaccharides from Chinese Herbal Lycium barbarum Induced Systemic and Local Immune Responses in H22 Tumor-Bearing Mice - Xiangliang Deng; Shuang Luo; Xia Luo; Minghua Hu; Fangli Ma; Yuanyuan Wang; Xiaoping Lai; Lian Zhou (Journal of Immunology Research)
Lycium barbarum polysaccharide (LBP) is isolated from the fruit of Chinese herbal Lycium barbarum. Previous studies had demonstrated that LBP could inhibit tumor growth and enhance the immunity in mice. However, the effect of LBP on systemic and local immune responses in vivo, especially on phenotypic and functional changes of T cells, is still largely unknown. In the present study, we investigated the effects of LBP on systemic and local T cell-dependent antitumor immune responses in H22 tumor-bearing mice. The results showed that LBP could inhibit the solid tumor growth in mice, but showed little effect on the body weight or spleen index. Furthermore, LBP could maintain high levels of T cells in peripheral blood (PB), tumor draining lymph node (TDLN), and tumor tissue, prevent the increase of Tregs while promote infiltration of CD8+ T cells in tumor tissue, inhibit the production of TGF-β1 and IL-10 in serum, decrease the exhaustion phenotype of T cells, and maintain cytotoxicity of lymphocytes. Taken together, our results demonstrated that LBP simultaneously induced systemic and local immune responses in H22 tumor-bearing mice by alleviating immunosuppression and maintaining antitumor immune responses in mice.